Kafkaesque Absurdity in the Aesthetics of Beckett and Giacometti (ENTHYMEMA, 2013)
The complex zone of what I refer to as the aesthetical absurd is examined in the works of Modernists Kafka, Giacometti, and Beckett. This aesthetic zone, addressed through cognitive poetics, exists between artistic notion, the artist’s ideal cognitive image, and the actual performance or resulting image born in reality. Artistic ideal is evaluated as the aesthetic image or notion that exists in a tentative nascent and emotive state, but one that the artist strives to produce in the world—to reconstruct from the cognitive zone of creativity—but at times fails to bring to completion or fruition. This ever present bifurcation between these two conflictive states leads to a new view of the Sisyphean absurd. Kafka stands as the beginning point of the discussion. His fragmented, at times incomplete, writing serves as a touchstone to position the aesthetics of the later Beckett and Giacometti, a sculptor. Beckett mirrors Kafka’s sensibility, and relates his negative aesthetic, one lacking or hiding any visible scaffolding for the artistic process. Beckett and Giacometti were friends and collaborated on crafting props for a staging of his signature play Waiting for Godot, a failed attempt. An assessment of the aesthetics of these three artists advances the understanding of their works in terms of the aesthetical absurd.
Keywords: Kafka; Giacometti; Beckett; aesthetics; absurd